Fighting Dry Mouth: An Interprofessional Opportunity - Louise Veselicky; Lauren Swager; Susan Morgan; Dani Dolin; Christina DeBiase; Kenneth Veselicky (Association of American Medical Colleges, 2013)
Abstract Introduction Dry mouth (xerostomia) is caused by medications, medical diseases, and medical treatments. Medications account for approximately 90% of xerostomia cases. With a growing population of people over 65, and many patients taking more than one medication, the consequences of dry mouth to the hard and soft tissues of the oral cavity are becoming one of the fastest growing health problems in our world today. It can affect an individual's quality of life by affecting their ability to eat, swallow, sleep comfortably, and speak. It is critical that all health care professionals develop competency in the area of xerostomia. Methods This case-based learning module presents information on the importance of saliva for normal body function; what happens when salivary function is reduced; what causes this reduction in saliva; and describes roles of the interdisciplinary team in recognition and management of this condition. The module is a PowerPoint recorded in Camtasia by two dentists, a pharmacist, and a physician/psychiatrist. The recording can be utilized by an individual or in groups. This submission contains four cases and an assessment tool with a separate file that contains the answers to the questions along with the explanation of the correct answers. Results Two of the authors of this module, a pharmacist and dentist, presented at the West Virginia Pharmacy meeting and a regional meeting that included pharmacists from West Virginia, Ohio, and Pennsylvania. Some of the comments on the written evaluation for these sessions included: "Informative," "Very good and helpful," "Liked the collaboration between pharmacy and dentistry," "Personal application to my practice and awareness of this issue when working with patients is critical." One pharmacist was in charge of protocol for a group of pharmacies in the state of Indiana and stated that she would develop protocol for counseling for dry mouth in her pharmacies. Many providers have now begun asking patients directly if they have been experiencing dry mouth and have reported shockingly high numbers of patients who say yes. Discussion The American Pharmacists Association, the American Dental Association, the Academy of General Dentistry, and the American Academy of Periodontology are currently working to expand awareness of the consequences of dry mouth and this is an effective interprofessional opportunity for achieving this goal. The interdisciplinary operation of the health care delivery system to anticipate, recognize, manage, and refer the sequelae of xerostomia will be essential.